YOUTH PHYSICAL ACTIVITY AND THE PROCESS OF PHYSICAL EDUCATION IN LUBLIN PROVINCE, POLAND - Wasilewska, Małgorzata; Bergier, Józef (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The research was conducted on a randomly chosen group of 916 students aged 16-18 in Lublin Province, Poland. The research was carried out in 2016 using the International Physical Activity Questionnaire, the extended version, and supplemented with additional questions regarding the students’ assessment of physical education lessons. The majority of students (77.4%) meet the requirements for a high level of physical activity, with the remaining 16.5% demonstrating moderate and only 6.1% − low level. There were no significant reductions of physical activity visible in the older age group, although in subsequent periods (in 16-18 year-olds), it was successively lower. The mean level of total physical activity in boys was 65566 MET[1] - min week, and it was significantly higher than in girls, i.e. 5345,5 MET-min/week. The vast majority of students (92.2%) participate in school physical education classes, and over 75% think that they like these activities. Students enrolled in physical education classes demonstrate a higher level of total physical activity (5960.5MET-min/week), in contrast to the non-participating ones (5637,2MET-min/week); however, no significant relationship has been found. Furthermore, it has been shown that girls and boys were willing to get involved in different physical activities. Apart from PE classes, boys would mainly get involved in football (23.2%), volleyball (15.5%), table tennis (13.0%), and swimming (12.5%). Girls would instead choose volleyball (14.7%), football (12.6%), swimming (9.4%) and gymnastics (8.9%). This favourable image of physical activity of students in the Polish schools in Lublin Province can contribute to the discussion of the place of physical activities in the modern school educational process.